1984
DOI: 10.1080/01904168409363189
|View full text |Cite
|
Sign up to set email alerts
|

Response of alfalfa to iron and boron in some Egyptian soils

Abstract: Broadcasting Fe increased alfalfa forage yield in calcareous soils, however, higher yield was obtained by using broadcasting and foliar application together. In sandy soil, broadcasting 24 kg Ferrous sulphate Ha -1 significantly decreased the yield while 12 kg Ferrous sulphate + 12 kg Borax Ha -1 produced the highest yield. The highest uptake of Fe by the alfalfa in calcareous soil was by the foliar application followed by combination of both methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Total dry matter yield during that season showed a numerical increase in yield but was not significant ( P > 0.05). Rannnah et al (1984), Haby and Leonard (2005), and Kheirkhah et al (2016) reported positive impacts of B on alfalfa production. However, our data showed B fertilization did not influence total yield of alfalfa in either year.…”
Section: Effect Of Boron On Yieldmentioning
confidence: 97%
“…Total dry matter yield during that season showed a numerical increase in yield but was not significant ( P > 0.05). Rannnah et al (1984), Haby and Leonard (2005), and Kheirkhah et al (2016) reported positive impacts of B on alfalfa production. However, our data showed B fertilization did not influence total yield of alfalfa in either year.…”
Section: Effect Of Boron On Yieldmentioning
confidence: 97%